An Android-Based Information System for Student Payment Billing - Muhammad Faizal Basri; Siti Sufaidah (NEWTON: Networking and Information Technology, 2025)
The advancement of information technology has encouraged schools to adopt digital payment systems. This study aims to develop a school billing application based on Android, integrated with the Midtrans Core API as an online transaction solution. The application is designed to simplify the payment process for parents and assist school administrators in recording and monitoring transactions automatically. The development process follows the Rapid Application Development (RAD) method, consisting of planning, design, rapid construction, and implementation stages. The backend is built using Laravel, while the mobile interface is developed with React Native. System testing is conducted using the Black Box Testing method to ensure that all features work as intended, including login, bill display, payment processing, and transaction reporting. The results show that the application improves efficiency and transparency in managing school payments. This solution enhances accessibility for parents and supports the digital transformation of school administration systems.